Perlindungan Perempuan Dan Anak Dalam Perspektif Hukum - Hasan, Ferdy; Dungga, Weny Almoravid; Abdussamad, Zamroni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Women and children are vulnerable to various forms of violence, including domestic violence, sexual harassment, sexual and economic exploitation, human trafficking and child labour. The purpose of this research is to find out how women and children are protected from a legal perspective. The type of research being carried out is normative legal research which is descriptive in nature about the protection of women and children from a legal perspective, namely by looking at events in society in terms of laws and the opinions of experts. This protection aims to ensure their security, human rights, welfare and healthy development. Although there have been various legal efforts to protect women and children, many challenges remain. Some of these challenges include lack of awareness, social stigma, lack of access to the justice system, and lack of resources to implement the law effectively